SIRT1 and metabolic syndrome - Mac-Marcjanek, Katarzyna; Wojcik, Marzena; Cypryk, Katarzyna (Menopause Review/Przegląd Menopauzalny, 2011)
Both obesity and type 2 diabetes mellitus, two major components of metabolic syndrome, become health epidemics in the world. Over the past decade, advances in understanding the role of some regulators participating in lipid and carbohydrate homeostasis have been made. Of them, SIRT1, the mammalian orthologue of the yeast Sir2 protein has been identified. SIRT1 is a nuclear NAD+-dependent deacetylase that targets many transcriptional modulators, including PPAR-α and -γ (peroxisome proliferator-activated receptors α and γ), PGC-1α (PPAR-γ coactivator-1α), FOXO (forkhead box O proteins), and nuclear factor κB (NF-κB), thereby this enzyme mediates a wide range of physiological processes like apoptosis, fat metabolism, glucose homeostasis, and neurodegeneration. In this article, we discuss how SIRT1 regulates lipid and carbohydrate metabolism, and insulin secretion in different metabolic organs/tissue, including liver, muscle, pancreas, and fat. Additionally, the role of this enzyme in reduction of inflammatory signalling is highlighted.